2021
DOI: 10.1017/s1368980021003426
|View full text |Cite
|
Sign up to set email alerts
|

Towards healthier food choices for hospital staff and visitors: impacts of a healthy food and drink policy implemented at scale in Australia

Abstract: Objective: To determine the impact of a healthy food and drink policy on hospital staff and visitors’ food purchasing behaviours, and their awareness and support for the changes introduced. Design: Two repeated cross-sectional surveys, consisting of intercept interviews and observations of food items purchased were conducted before (March-July 2018) and after (April-June 2019) the target date for implementation of 13 food and drink practices (31 December 2018). Food purchases were coded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…10,29 Our study reveals factors central to interpreting outcomes found in related Framework evaluation studies. 14,19,20 Many retailers who adopted practices early – and even those whose contracts with the health service did not include conditions to achieve Framework practices – were motivated to succeed. This was prompted by aligned values, or anticipated opportunities within a dynamic market and the confidence or perceived leverage to change demand.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10,29 Our study reveals factors central to interpreting outcomes found in related Framework evaluation studies. 14,19,20 Many retailers who adopted practices early – and even those whose contracts with the health service did not include conditions to achieve Framework practices – were motivated to succeed. This was prompted by aligned values, or anticipated opportunities within a dynamic market and the confidence or perceived leverage to change demand.…”
Section: Discussionmentioning
confidence: 99%
“…26 From the possible 18 LHDs, 11 were selected as the sampling frame from which stakeholders were identified. Nine LHDs had been randomly selected previously as part of a related larger evaluation study 19 and the remaining two were purposively selected to increase regional LHD representation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations